2021
DOI: 10.3390/medicina57070718
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Validation of Free Flaps in Acute and Reconstructive Burn Care

Abstract: Microsurgical free flap reconstruction in acute burn care offers the option of reconstructing even challenging defects in a single stage procedure. Due to altered rheological and hemodynamic conditions in severely burned patients, it bears the risk of a higher complication rate compared to microsurgical reconstruction in other patients. To avoid failure, appropriate indications for free flap reconstruction should be reviewed thoroughly. Several aspects concerning timing of the procedure, individual flap choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…After applying inclusion and exclusion criteria, 31 articles were included in the qualitative and quantitative synthesis. 8–10,18–46 A flow chart of the study inclusion process and the reasons justifying the exclusion of the 166 studies are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After applying inclusion and exclusion criteria, 31 articles were included in the qualitative and quantitative synthesis. 8–10,18–46 A flow chart of the study inclusion process and the reasons justifying the exclusion of the 166 studies are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6] However, in cases of extensive exposure of critical structures (such as the bone, cartilage, tendons, or neurovascular bundles), flap reconstruction proves to be a more appropriate choice. 7,8 It allows for a single-stage reconstruction, thus reducing healing time and hospital period. 8,9 Thus, flap reconstruction may decrease the complications associated with delayed wound healing, which include dehydration of exposed structures and infection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los avances en tratamiento, las mejoras en la sobrevivencia de los pacientes gran quemado y el mejor entrenamiento en microcirugía con un aumento del número y tipos de colgajos y el florecimiento de la técnica, permitieron que este tipo de cirugía fuera un tratamiento seguro y factible en este contexto de pacientes, en relación con los resultados y tasa de complicaciones. A pesar de la condición clínica crítica y desafiante de estos pacientes, actualmente, se reconoce al CM como una herramienta esencial para la víctima de quemaduras, más específicamente, en las quemaduras de alto voltaje, donde juega un rol importante en el salvataje de la extremidad 6 o como primera opción de tratamiento ante defectos complejos con exposición ósea, de nervios o tendones 16 .…”
Section: Discussionunclassified